The Need For Formation of Knowledge on The Effective Use Of Water Resources in Young People in The Process of Globalization. (In The Example Of The Aral Sea) - Sharofiddin Shukurjon Ogli Shomurotov (International Journal on Human-Computing Studies, 2021)
The article deals with the issues of intensive development of irrigation systems, effective management of water resources and improvement of irrigation infrastructure, application of agro-technical measures in agriculture, implementation of innovations to improve the reclamation of irrigated lands, efficient and rational use of water resources illuminated